Cell growth and alpha-amylase production characteristics of Bacillus subtilis - Dercová, K; Augustín, J; Krajcová, D (Folia microbiologica, 1992)
Growth, differential rate of alpha-amylase synthesis and production characteristics of Bacillus subtilis DP 1 (isolate from starch materials) in comparison with 10 Bacillus strains were examined in batch fermentation. The effect of the carbon and nitrogen source was evaluated with regard to cell growth and enzyme production. The pH optimum of enzyme activity was 6.5 and temperature optimum of 60 degrees C.
Keywords: dusík; Bacillus subtilis; uhlík; koncentrace vodíkových iontů; Temperature; alfa-amylasy; Culture Media; alpha-Amylases; kinetika; teplota; Hydrogen-Ion Concentration; Cell Division; buněčné dělení; Kinetics; kultivační média; Carbon; Nitrogen